Perinatal Ureaplasma Exposure Is Associated With Increased Risk of Late Onset Sepsis and Imbalanced Inflammation in Preterm Infants and May Add to Lung Injury - Glaser, Kirsten; Gradzka-Luczewska, Anna; Szymankiewicz-Breborowicz, Marta; Kawczynska-Leda, Natalia; Henrich, Birgit; Waaga-Gasser, Ana Maria; Speer, Christian P. (Frontiers in Cellular and Infection Microbiology, 2019)
Background: Controversy remains concerning the impact of Ureaplasma on preterm neonatal morbidity. Methods: Prospective single-center study in very low birth weight infants <30 weeks’ gestation. Cord blood and initial nasopharyngeal swabs were screened for Ureaplasma parvum and U. urealyticum using culture technique and polymerase chain reaction. Neonatal outcomes were followed until death or discharge. Multi-analyte immunoassay provided cord blood levels of inflammatory markers. Using multivariate regression analyses, perinatal Ureaplasma exposure was evaluated as risk factor for the development of bronchopulmonary dysplasia (BPD), other neonatal morbidities until discharge and systemic inflammation at admission. Results: 40/103 (39%) infants were positive for Ureaplasma in one or both specimens, with U. parvum being the predominant species. While exposure to Ureaplasma alone was not associated with BPD, we found an increased risk of BPD in Ureaplasma-positive infants ventilated ≥5 days (OR 1.64; 95% CI 0.1222.98; p=.009). Presence of Ureaplasma was associated with a 7-fold risk of late onset sepsis (LOS) (95% CI 1.8027.39; p=.014). Moreover, Ureaplasma-positive infants had higher I/T ratios (b 0.39; 95% CI 0.08-0.71; p=.014), increased levels of interleukin (IL)-17 (b 0.16; 95% CI 0.020.30; p=.025) and matrix metalloproteinase 8 (b 0.77; 95% CI 0.101.44; p=0.020), decreased levels of IL-10 (b -0.77; 95% CI -1.58-0.01; p=.043) and increased ratios of Tumor necrosis factor-α, IL-8 and IL-17 to anti-inflammatory IL-10 (p=.003, p=.012, p<.001). Conclusions: Positive Ureaplasma screening was not associated with BPD. However, exposure contributed to BPD in infants ventilated ≥5 days and conferred an increased risk of LOS and imbalanced inflammatory cytokine responses.